Oil Price Shocks, Agriculture and Household Welfare in Nigeria: Results From an Economy-Wide Model - Nkang M. Nkang (European Scientific Journal, ESJ, 2018)
Following the recent plunge in the price of crude oil in the international market and its attendant implications on oil-exporting countries, this paper simulated the impact of a fifty per cent decline in world oil price on agriculture and household welfare using a general equilibrium model, and data from a social accounting matrix (SAM) for Nigeria. Results show that gross domestic output and supply of composites in the agriculture sectors increased substantially, causing agriculture prices to decline. Furthermore, the shock reduced incomes/expenditure in all household groups except urban-north households that recorded an increase. We therefore conclude that lower oil prices may not necessarily lead to output losses, but could boost output in other sectors, engendering diversification of the export base. Also, targeted interventions would prove more effective in mitigating the negative impact of oil price shocks on households than general palliative measures based on the results of the study.